FRASA DAN KONSTRUKSI FRASA BAHASA KATINGAN - Elisten Parulian Sigiro (SUAR BETANG, 2017)
This research examines the rules and construction of the Katingan language phrase with the purpose of the description of the rules and construction of the Katingan language phrase. Therefore, the method used in this research is descriptive qualitative method because the method and technique of this research reflects reality in the field as they are. In terms of provision of research data used simak and cakap method with basic and advanced techniques. The results of this study indicate that the use of verbal, adjective, pronominal, adverbial, prepositional, and numerical phrases in Katingan is highly productive. This is demonstrated by the diversity of verbal, adjunctive, pronominal, adverbial, prepositional, and numerical Katingan language constructs